(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Between the years 1980-2000 Perú lived a period characterized by the violence of its internal armed conflict (CAI) and the Fuji- mori dictatorship. The Lugar de la Memoria, la Tolerancia y la Inclusión Social (LUM) is a space that encourages reflexion about those years. The construction of LUM was not free of debates and polemics. The aim of the present work is to present a contex- tualization of its construction, reflect about those debates, and then briefly analyze its current museography. To pay attention to the discussions that surrounded this construction allows us to get a sense of the problem that means a space of memory that is the result of a memory policy, such as LUM.